Effects of hexavalent chromium on intestinal histology and microbiota in Bufo gargarizans tadpoles. (February 2019) - Yao, Qiong; Yang, Hongyu; Wang, Xianchan; Wang, Hongyuan
Abstract: Chromium is detrimental heavy metal pollutants and can enter and affect aquatic organisms. In our experiment, B. gargarizans embryos were chronically exposed in different concentrations of Cr (VI) (0, 13, 104, and 416 μg Cr 6+ L −1 ) until reached Gosner stage 38. We measured morphological parameters of the body and intestine of B. gargarizans tadpoles, and examined alteration of intestinal tissue. Furthermore, we analyzed the intestinal microbial community of B. gargarizans tadpoles using 16S rRNA gene amplicon sequencing. Our research demonstrated that Cr (VI) exposure caused alteration of intestinal tissue structure in 416 μg Cr 6+ L −1 treatment groups. Total body length, body wet weight, intestinal length and wet weight of B. gargarizans tadpoles were significantly declined at 416 μg Cr 6+ L −1 . In addition, 16S rRNA gene sequencing revealed that Cr (VI) exposure significantly altered the intestinal microbiota diversity and composition, and perturbed the community structure of the microbiota. As for the intestinal microbiota, at the phylum level, Fusobacteria significantly changed in all Cr (VI) treated groups. Saccharibacteria and TM6_Dependentiae were detected only in the high dose exposure groups. At the genus level, Aeromonas was significantly decreased in Cr (VI) treated groups. According to the results of functional prediction, Cr (VI) exposure affected metabolism and increased risk of disease by inducing the alterations of intestinal microbiota structure. Taken together, the present study provide a new framework elucidating the toxic effects Cr (VI) exposure on B. gargarizans tadpoles associated with intestinal histology and microbiota. Highlights: Cr (VI) exposure caused alteration of intestinal tissue structure. Cr (VI) exposure altered the intestinal microbiota diversity and composition. Cr (VI) exposure affected metabolism and increased risk of disease.